Effectiveness of Google Classroom in Chemistry Learning on Stoichiometry Topic Viewed from Students’ Learning Motivation - Emi Sulmeni; Daud K. Walanda (Universitas Tadulako, 2020)
This study aimed to determine the effectiveness of using google classroom in chemistry learning in terms of student learning motivation in MAN 2 Parigi, Sulawesi Tengah Indonesia. The sample in this study was students in class X MIA 2 (n = 23). The data analysis technique was the effect size d Cohen test, the value was 0.86 which had a very large effect category. This influence can be seen from students' learning motivation which increased with an average score of 3.70 which had a very good category. Based on these data it can be concluded that Google classroom affected the students’ learning results and learning motivation.